Logistics of patient evacuation in response to disease Outbreaks: Critical considerations for transportation planning - Maziar Yazdani; Milad Haghani (Transportation Research Interdisciplinary Perspectives, 2023)
The recent outbreaks of diseases have emphasized the importance of having robust decision-making models in place to aid in the evacuation of patients, particularly from overwhelmed hospitals to alternative facilities. The sudden surge of patients during an outbreak can quickly deplete a hospital's resources, leading to compromised healthcare delivery and an increase in mortality rates. Evacuating patients to other hospitals can alleviate the burden on a single facility, but numerous factors need to be considered when making evacuation decisions, including patient acuity, transportation logistics, and bed availability at other facilities. Despite the critical role of patient evacuation in disease outbreaks, there has been a lack of systematic and comprehensive research on developing decision-making models that identify the critical factors. This paper aims to bridge this gap by providing the key factors that should be considered when creating decision models for patient evacuation in response to contagious disease outbreaks. The findings reveal that decision-making processes are influenced by a multitude of factors, including patient numbers and classifications, staff scheduling and assignments, resource availability for transportation, road traffic conditions, capacities and numbers of evacuation and receiving hospitals, as well as the behaviour of disease outbreaks. These findings provide practical insights for relevant authorities to optimize emergency strategies during disease outbreaks and enhance the overall resilience of the healthcare system against external disruptions.